QUALITY OF HUMAN DEVELOPMENT INDEX (HDI) IN MUSLIM COUNTRIES (CASE STUDY OF OIC MEMBERS) - MUHAMMAD GHAFUR WIBOWO (Universitas Islam Negeri Imam Bonjol Padang, 2019)
This study analyzes factors or variables that effect of human development index (HDI) in Muslim countries, a case study of the Organization of Islamic Cooperation (OIC) member countries. The data of 33 selected OIC member countries from 2007-2016 were analyzed using panel data regression analysis. The entire models show the significant influence of some independent variables to the level of HDI in Muslim countries. However, a variable number of the population contributes positively to HDI in all models. Unfortunately, foreign direct investment (FDI) does not add to the increasing of HDI; this is the biggest challenge faced by the government in various Muslim countries. While government fiscal policy reflected in government spending (G) contributes positively to HDI in OIC member countries.